Proposta metodológica de ensino da Matemática no 6º ano, a partir da música - RAFAEL, Diego do Nascimento (2022)
Musicality is an enriching element for teaching Mathematics, as it includes the tripod of art, emotion and reason. The present work on the study of the theme “Methodological proposal for teaching Mathematics in the 6th year, based on music, takes as its motivation the questions: What is the relationship between music and the teaching of Mathematics? What musical elements can be related to the contents of Mathematics? What influence musicality with the teaching of Mathematics can have on the development of mathematical skills and competences? The general objective is to analyze the relationship between music and mathematical content and knowledge in teaching and learning in the final years of elementary school. The research developed has a qualitative approach, in which the investigation procedures were based on bibliographic research, in which the instruments used in the bibliographic review were official documents, books, periodicals, articles and blog. The results showed that the study was not restricted to data related to school teaching processes, above all, it sought to promote a contribution to the training of teachers, so that Mathematics teachers can have understanding and motivation to include interdisciplinary teaching activities, and music can be an excellent methodology for teaching Mathematics.